Inversion of Moho topography in Taiwan using improved Parker-Oldenburg method - Yu, Hangtao; Wen, Mingming; Xu, Chuang (Frontiers in Earth Science, 2025)
Taiwan is located at the junction between the Philippine Sea Plate and the Eurasian Plate, with intense tectonic movements in the region. A more accurate Moho topography model is significant for the study of the intrinsic genesis within Taiwan’s orogenic movement and the subduction pattern of the Philippine Sea plate. Previously, there were two key issues in Moho topographic inversion that needed to be solved, i.e., extracting signals originating from Moho topography and estimating more accurate inversion parameters. To solve these two issues, we use wavelet multi-scale analysis to separate the gravity signals at different depths and extract the signals originating from Moho topography from them. Then, more accurate inversion parameters are estimated using simulated annealing with available seismic data as constraints. On this basis, a more refined Moho topography of Taiwan is inverted. The Moho topography shows that most of Taiwan has a Moho topography of about 28 km, with the highest point slightly above 30 km and the lowest point between 20 and 25 km. Based on the Moho topography contours, we estimate that subduction of the Philippine Sea plate ends at the 25 km contour, in the middle of the Coastal Range, near 23.5°N. This is one of the possible reasons for the high frequency of earthquakes in the region. Comparing with the existing seismic control points, the corresponding root-mean-square error of our Moho model is 4.98 km smaller than the CRUST 1.0 model, which indicates that our Moho model is more accurate and realistic.